FATWA DAN AKTUALISASI HUKUM ISLAM DI INDONESIA - Suhufi, Muhammad (DIKTUM: Jurnal Syariah dan Hukum, 2010)
Religious authority is an extremely wide concept which may become manifest in an infinite variety of ways. It may be embodied in certain notions, in texts, in individual, in groups of persons, and in institutions in the widest sense of the word. For this reason, if a scholar wants to write an article about religious authority, it is essential to make a conceptual breakdown of the idea in order to write meaningfully on the subject. In the present contribution I would like to study the concept of religious authority in Indonesia through the vehicle of the Islamic institution of iftÃ¢, delivering of a fatwa. In its classical form a fatwa consists of two parts: a question addressed to a scholar of Islam about a particular topic which has been addressed to him by one or more believers in order to obtain the scholars opinion about this topic from the perspective of Islamic law. This part of the fatwa is called istiftÃ¢ , while the person who raises the issue is called the mustaftÃ®. istiftÃ¢ , The second part of the fatwa is the actual answer given by the scholar, called the mufti , â fatwa -giverâ. The language of the fatwa is very formal and formulaic. In the fatwa, the mufti pronounces about issues which are of topical interest to the believer, by sang mufti referring to the standard manuals of jurisprudence. These topics often deal with ritual issues, but in principle may deal with any conceivable topic, including social and political issues or problems arising from the application and use of modern technology. In the course of time, fatwaâs issued by important mufti s have been collected and hese collections can be regarded as manuals of applied legal science. In short, it can be said that fatwa s constitute a meeting, and in many cases a compromise, between the ideals of the Holy Law, as expressed by the ulamÃ¢, and the reality of daily life, as experienced by the believers. For a study of the working of religious authority the fatwa is useful, because the fatwa is an important instrument through which the ulamÃ¢